2010
DOI: 10.1057/grir.2010.7
|View full text |Cite
|
Sign up to set email alerts
|

(S,s)-adjustment Strategies and Hedging under Markovian Dynamics

Abstract: We study the destabilizing effect of hedging strategies under Markovian dynamics with transaction costs. Once transaction costs are taken into account, continuous portfolio rehedging is no longer an optimal strategy. Using a non-optimizing (local in time) strategy for portfolio rebalancing, explicit dynamics for the price of the underlying asset are derived, focusing in particular on excess volatility and feedback effects of these portfolio insurance strategies. Moreover, it is shown how these latter depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…20 In the previous volumes of the GRIR, several papers, not mentioned by the authors, have looked at the insured's VaR constraint in the optimal insurance decision. 21 Agliardi and Andergassen (2011). 22 In their paper, Derman and Taleb (2005) have shown that dynamic hedging is neither strictly required nor strictly necessary for plausibly valuing options.…”
Section: Demutualisation and Performance Of Property-liability Insuramentioning
confidence: 99%
“…20 In the previous volumes of the GRIR, several papers, not mentioned by the authors, have looked at the insured's VaR constraint in the optimal insurance decision. 21 Agliardi and Andergassen (2011). 22 In their paper, Derman and Taleb (2005) have shown that dynamic hedging is neither strictly required nor strictly necessary for plausibly valuing options.…”
Section: Demutualisation and Performance Of Property-liability Insuramentioning
confidence: 99%